VLSI implementation of a novel algorithm for binarynegabinary code conversion - Bajpai R.; Zaghloul M.; Balasubramanian S.K. (My University, 2025)
A code converter establishes compatibility between two systems using different codes. Negabinary number system is adopted for unique applications where it provides certain definite advantages over binary number system. In this paper, we have presented VLSI implementation of a novel algorithm that can be used for the conversion of numbers from binary to negabinary number system and vice-versa. This algorithm is faster, consumes less power and more generic than all the algorithms which have been proposed earlier. ©2008 IEEE.